LASK (Ljubljanski akademski sportni klub) - Pavlin, Tomaž (Šport (Ljubljana), 2019)
The acronym LASK conceals a forgotten and lost sport story that coincides with the dramatic period for sports and for the University of Ljubljana after World War I, after the establishment of the state of Yugoslavia. Based on the preserved minutes of the club committee's meetings between 1920 and 1923, the article unveils the story about the athletes who studied at the then relatively new University of Ljubljana and dedicated their leisure time to sport. In the then Ljubljana, characterised by nation-wide euphoria and the spirit of "liberation", sport had been revived and the University of Ljubljana's students made a historical contribution in this respect. The LASK was founded in 1920 and operated during a short five-year period, whereas the members pursued their sports careers either in the Primorje club or in other Ljubljana- based sports clubs. The minutes are a valuable historical sport document and one of the few of this kind from the period between the two World Wars, and they put emphasis on the description of the organisation in the first three years of development.
Keywords: academics; akademiki; history; LASK; sport; students; šport; študenti; University of Ljubljana; Univerza v Ljubljani; zgodovina športa